The Architectural Style of Masjid Agung At-Taqwa, Kutacane, Southeast Aceh (2016-2023) - Yusra Dewi Siregar; Nisrina Zulfa (Yupa: Historical Studies Journal, 2023)
This article aims to discuss the architectural style of the At-Taqwa Great Mosque in Kutacane, Southeast Aceh, during the period of 2016 to 2023. The study follows a qualitative research design with a descriptive approach. The research method used in this study is historical research. Data collection was conducted through interviews and observations. The results indicate that Islamic architecture is a captivating style that exemplifies the beauty of each building. Each detail contains a symbolic element with a significant meaning. An architectural work takes the form of a building, commonly referred to as a cultural symbol and also considered a work of art. Likewise, the architectural works within the At-Taqwa Great Mosque building combine styles from various local and international influences, resulting in a stunning work of art.